Pendidikan Akhlak sebagai Tuntutan Masa Depan Anak - Zainudin Zainudin (Institut Agama Islam Negeri (IAIN) Tulungagung, 2013)
Teaching morality to children must be conducted seriously. Morality is one of essential matters in this country because it has close relationship with norms in society. When people’ morality is under control, there is a peace in the society. Therefore, in teaching children, teachers should incorporate morality every time and everywhere.The main purpose is, of course, to gain prosperity among people.